Susan Bayó Belenguer, Eiléan Ní Chuilleaniáin and Cormac Ó Cuilleanáin (eds), Translation. Right or Wrong (Altre Modernità, 2013)
(Dublin, Four Courts Press, 2013, pp. 299, ISBN 978-1-84682-372-5)di Ilaria Parini